PANCASILA SEBAGAI LANDASAN ETIS DALAM INOVASI ILMU PENGETAHUAN DAN TEKNOLOGI - Eguita, Shin (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Entering the era of the industrial revolution 4.0, our lives are now oriented towards the digital industrial world, including in the field of science and technology (IPTEK). The industrial revolution 4.0 requires every individual to quickly adapt and develop technological literacy, data, and human resources. These three aspects are the basic capital in developing various individual competencies. The development and progress of science and technology today depends on the mastery of these three literacies. However, if the development of science and technology is not based on a strong foundation of national values, there will be more negative impacts than positive impacts. The misuse of science and technology can threaten human survival in the future. Therefore, efforts are needed to counteract the various negative potentials of the development of science and technology, one of which relies on Pancasila. Pancasila is not only the basis of the state, the guideline of life, and the unifier of the Indonesian nation, but also a guide in all aspects of life, including in the development of science and technology. The values contained in Pancasila must be used as the main guideline in the development of science and technology. By making Pancasila the basis of science and technology development, it is expected to have a broad positive impact on the welfare of the Indonesian people. Although science and technology can develop and advance, it must be balanced with efforts to maintain and apply the noble values of the nation's ideology in all aspects of life.